Future Trends of Building Energy Management Systems: A Scientific Mapping Approach (LACCEI, 2024)
The objective of this review work was to establish a scientific map of the identification of future trends of the application of building energy management systems (BEMS) in energy control. For this, the Scopus database was used to collect documents that were used in the analysis of the bibliometric review work. Consequently, SciMAT was used to carry out the complete bibliometric process, from data processing to analysis. The results indicate that the most challenging issues of BEMS is to maximize energy efficiency, minimizing losses and energy consumption. This has been adequately addressed with the concept of the Internet of Things (IoT). However, the trend points to the thematic concept of the Internet of Energy (IoE) in energy monitoring and control in buildings through two-way communication between the smart grid and BEMS. Therefore, this review highlights IoT and IoE- based energy management as key technologies to support the future advanced implementation of BEMS.